The Influence of Social Media Exposure and Influencers on Generation Z's Impulsive Buying of Fast Fashion Through Brand Awareness - Ni Made Dwi Yanti; Lalu Edy Herman Mulyono (LP2M IAIN Palopo, 2026)
This study aims to examine the influence of social media exposure and influencers on impulsive buying among Generation Z in the context of fast fashion products, with brand awareness as a mediating variable. The background of this study is based on the increasing trend of spontaneous purchases triggered by social media content and promotional activities carried out by influencers on social media platforms such as Instagram and TikTok. The research approach used a quantitative method with a survey design. The population for this study was fast fashion product buyers, with a sample size of 130 respondents. Data were obtained using a purposive sampling method, with the criteria being Generation Z aged 18–27 who are active on social media, follow at least one influencer, and have purchased a fast fashion product in the past six months. Data analysis was conducted using the SEMPLS software approach. The results showed that social media exposure and influencers have a direct positive and significant influence on impulsive buying. However, exposure to social media and influencers did not have a positive and significant influence on impulsive buying through brand awareness. Furthermore, brand awareness also did not have a positive and significant influence on impulsive buying. These results indicate that Generation Z tends to make impulsive purchases due to factors other than brand awareness.